2010
DOI: 10.1021/es100797r
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Loading and Transport ofEscherichia coliat an Embayed Beach in Lake Michigan

Abstract: A Chicago beach in southwest Lake Michigan was revisited to determine the influence of nearshore hydrodynamic effects on the variability of Escherichia coli (E. coli) concentration in both knee-deep and offshore waters. Explanatory variables that could be used for identifying potential bacteria loading mechanisms, such as bed shear stress due to a combined wave-current boundary layer and wave runup on the beach surface, were derived from an existing wave and current database. The derived hydrodynamic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 27 publications
(37 reference statements)
1
63
1
Order By: Relevance
“…In addition to marine water bodies, the POM has been successfully applied to the entire Lake Michigan (Beletsky and Schwab 2001) as well as considerably smaller areas, such as coastal waters in southern Lake Michigan (Thupaki et al 2010). In contrast to open coastal waters (Thupaki et al 2010), the embayed 63rd Street Beach has interesting flow structures, such as flow separation, recirculation (gyres) due to the blockage effect of the breakwaters, and the formation of turbulent shear layer near the opening of the embayment (Ge et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to marine water bodies, the POM has been successfully applied to the entire Lake Michigan (Beletsky and Schwab 2001) as well as considerably smaller areas, such as coastal waters in southern Lake Michigan (Thupaki et al 2010). In contrast to open coastal waters (Thupaki et al 2010), the embayed 63rd Street Beach has interesting flow structures, such as flow separation, recirculation (gyres) due to the blockage effect of the breakwaters, and the formation of turbulent shear layer near the opening of the embayment (Ge et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that beach sand may serve as a reservoir for pathogens harmful to human health and indicator microbes that can be released into surrounding waters through tidal action or run-off (Alm et al, 2003;Whitman and Nevers, 2003;Boehm and Weisberg, 2005;Beversdorf et al, 2007;Colford et al, 2007;Fleisher et al, 2010;Ge et al, 2010;Sinigalliano et al, 2010;Abdelzaher et al, 2010). Several authors have reported that both indicator bacteria and potential pathogens occur in beach sands of both freshwater and marine environments (Sanchez et al, 1986;Ghinsberg et al, 1994Ghinsberg et al, , 1995Obiri-Danso and Jones, 2000;Desmarais et al, 2002;Sato et al, 2005;Vantarakis et al, 2005;Beversdorf et al, 2007;Bonilla et al, 2007;Vogel et al, 2007;Hartz et al, 2008;Abdelzaher et al, 2010).…”
Section: Bacteriamentioning
confidence: 99%
“…However, contamination of beach sands by pollution in the water has also been suggested (9). Bacteria in beach sands may also enter the water column via overbeach transport, where tidal events or wave action release bacteria attached to sand particles or those residing in interstitial spaces and these bacteria then enter the water directly (10,11). Alternatively, throughbeach transport can also occur when bacteria in unsaturated sands are mobilized downward due to tidal or wave action, enter the groundwater, and are transported via subterranean discharge to the water column (3,12).…”
mentioning
confidence: 99%